2021
DOI: 10.20945/2359-3997000000376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodine supplementation in pregnancy on neurocognitive development on offspring in iodine deficiency areas: a systematic review

Abstract: Objective: To investigate the effect of iodine supplementation during gestation on the neurocognitive development of children in areas where iodine deficiency is common. Materials and methods: Based on the PRISMA methodology, we conducted the search for articles in the PubMed, LILACS and Scopus databases, between March and April 2020, without limitation of dates. We used descriptors in English, Portuguese, and Spanish, without filters. Four clinical trials and four cohort articles were included in the review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…A positive association between preconception maternal iodine status and the cognitive function of the offspring at the age of 6–7 years could be demonstrated [ 265 ]. In contrast, meta-analyses of iodine supplementation starting during pregnancy found no effect on child neurodevelopment [ 196 , 264 , 269 , 270 , 271 , 272 ]. The lack of beneficial effects of iodine supplementation, typically after the first trimester, bypasses the critical period of development early in gestation.…”
Section: Resultsmentioning
confidence: 99%
“…A positive association between preconception maternal iodine status and the cognitive function of the offspring at the age of 6–7 years could be demonstrated [ 265 ]. In contrast, meta-analyses of iodine supplementation starting during pregnancy found no effect on child neurodevelopment [ 196 , 264 , 269 , 270 , 271 , 272 ]. The lack of beneficial effects of iodine supplementation, typically after the first trimester, bypasses the critical period of development early in gestation.…”
Section: Resultsmentioning
confidence: 99%
“…A 2021 systematic review evaluating three RCTs [60,77,78] and one nonrandomized trial [76] and four observational cohorts [77][78][79][80] found no significant improvement in children's mental development index and behavioral development index in the supplemented group [81]. Psychomotor development index showed improvement in the poorer gross motor skills and differences in response time to sound in the supplemented group [81].…”
Section: Maternal Iodine Supplementation and Child Neurodevelopmental...mentioning
confidence: 99%
“…A 2021 systematic review evaluating three RCTs [60,77,78] and one nonrandomized trial [76] and four observational cohorts [77][78][79][80] found no significant improvement in children's mental development index and behavioral development index in the supplemented group [81]. Psychomotor development index showed improvement in the poorer gross motor skills and differences in response time to sound in the supplemented group [81]. A 2021 meta-analysis of three trials [60,77,82] found no differences observed in cognitive, language, or motor development and did not demonstrate any clear benefit on infant neurocognitive outcomes with MIS of MMID patients [57 && ].…”
Section: Maternal Iodine Supplementation and Child Neurodevelopmental...mentioning
confidence: 99%
“…Iodine is an indispensable nutrient for the synthesis of the thyroid hormones, triiodothyronine and thyroxine, necessary for normal growth, development, and metabolism during pregnancy, childhood, and throughout life [1][2][3].…”
Section: Introductionmentioning
confidence: 99%